Book review: “It Starts with the Egg” by Rebecca Fett - A. D. Makatsariya (Акушерство, гинекология и репродукция, 2019)
The licensed edition of Rebecca Fett's book, “It Starts with the Egg” has been published in Russian. Given its medical contents, it seems important to evaluate the information contained in the book from the perspective of a practicing obstetrician-gynecologist, focusing on the problem of miscarriage and pregravid preparation. Importantly, the book is based on evidence-based medicine: although the book is intended for a wide scope of readers, it contains a list of primary references similarly to that in peer-reviewed journals.The author analyzed and summarized the data from over 60 scientific articles. Although based on primary academic sources, the author used a simple and understandable language to explain the complex pathogenesis of infertility and the manipulations used in the assisted reproductive technology (ART).The book consists of 3 parts; each of them contains several chapters reviewing the causes of reproductive disorders and the ways to correct them. The first part addresses the reasons for poor quality of women’s eggs. The second part describes nutraceuticals and dietary supplements that can improve the quality of eggs. The third part of the book examines the diet, which helps improve this quality. A step-by-step action plan for improving reproductive function is also presented. The basic plan is suitable for those who are just thinking about pregnancy and those who have no reason to expect any difficulties, as well as for couples who have been struggling with infertility for several years. The mid-level plan is intended for those who already have some concerns about conceiving, but are not yet aware of personal problems with their reproductive function, as well as for women with polycystic ovary syndrome (PCOS) or irregular ovulation. The plan for those having serious problems is intended for women with recurrent miscarriage, as well as for couples with a decrease in the ovarian reserve who are trying to get pregnant using in vitro fertilization (IVF).Despite some remarks regarding the role of vitamin D and magnesium in pregravid preparation, the book contains a large number of useful and balanced recommendations that can improve the woman’s health and increase her chances to get pregnant and give birth to a healthy baby. Therefore, the book can be recommended for a wide range of readers.